Capital Flow Measures : Structural or Cyclical Policy Tools? - Gupta, Poonam; Masetti, Oliver (World Bank, Washington, DC, 2018)
This paper analyzes the use of capital flow measures in emerging markets. Drawing on a specially compiled new database of capital flow measures, it establishes that policy makers in emerging market economies do not use capital flow measures as an active tool at business cycle frequency. While there is a general trend toward the liberalization of capital accounts, the use of capital flow measures as a countercyclical policy tool is rather sporadic. Instead, countries show a distinct preference for using monetary policy, exchange rate adjustments, macro prudential measures, and adjustments in external reserves to modulate the impacts of domestic business cycles, international liquidity cycles, and shocks to capital flows. Regulation of different kinds of capital flows -- resident and nonresident flows; inflows and outflows; and foreign direct investment, portfolio, and banking sector flows -- is changed infrequently and is acyclical to domestic business and external liquidity cycles.